2023
DOI: 10.1007/s11069-023-06114-7
|View full text |Cite
|
Sign up to set email alerts
|

Insights into volcanic hazards and plume chemistry from multi-parameter observations: the eruptions of Fimmvörðuháls and Eyjafjallajökull (2010) and Holuhraun (2014–2015)

Amy Donovan,
Melissa Pfeffer,
Talfan Barnie
et al.

Abstract: The eruptions of Eyjafjallajökull volcano in 2010 (including its initial effusive phase at Fimmvörðuháls and its later explosive phase from the central volcano) and Bárðarbunga volcano in 2014–2015 (at Holuhraun) were widely reported. Here, we report on complementary, interdisciplinary observations made of the eruptive gases and lavas that shed light on the processes and atmospheric impacts of the eruptions, and afford an intercomparison of contrasting eruptive styles and hazards. We find that (i) consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…This is a non-peer reviewed manuscript that has been submitted to Geochemistry, Geophysics, Geosystems 8. The petrological method also neglects post-eruptive outgassing from cooling lava, which is an additional source of volcanic pollution (Óskarsson et al, 1984;Thordarson et al, 1996;Simmons et al, 2017;Pfeffer et al, 2018;Sigmarsson et al, 2020;Donovan et al, 2023). This process disproportionately affects F and Cl, which only reach melt saturation as their concentrations in residual melts are driven up by microlite crystallization in cooling lava fields.…”
Section: Caveats and Sources Of Error Of The Petrological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a non-peer reviewed manuscript that has been submitted to Geochemistry, Geophysics, Geosystems 8. The petrological method also neglects post-eruptive outgassing from cooling lava, which is an additional source of volcanic pollution (Óskarsson et al, 1984;Thordarson et al, 1996;Simmons et al, 2017;Pfeffer et al, 2018;Sigmarsson et al, 2020;Donovan et al, 2023). This process disproportionately affects F and Cl, which only reach melt saturation as their concentrations in residual melts are driven up by microlite crystallization in cooling lava fields.…”
Section: Caveats and Sources Of Error Of The Petrological Methodsmentioning
confidence: 99%
“…Slow diffusivity of S in silicate melts may cause disequilibrium degassing (Lerner et al, 2021), which may explain commonly observed matrix glass S contents above the solubility limit of melts at surface pressures. The residual sulfur is progressively degassed from a cooling lava field, as seen in progressively waning S concentrations in matrix glasses with increasing distance to the vent and measurable SO2 degassing of lava fields observed by field measurements ( (Lerner et al, 2021, Donovan et al, 2023. For this reason, we consider ΔSmax to be a more reliable indicator of total SO2 release.…”
Section: Caveats and Sources Of Error Of The Petrological Methodsmentioning
confidence: 99%
“…Slow diffusivity of S in silicate melts may cause disequilibrium degassing (Lerner et al, 2021), which may explain commonly observed MG S contents above the vapor solubility limit of melts at surface pressures. The residual sulfur is progressively degassed from a cooling lava field, as seen in progressively waning S concentrations in matrix glasses with increasing distance to the vent and measurable SO 2 degassing of lava fields observed by field measurements (Donovan et al, 2023;Lerner et al, 2021). For this reason, we consider ΔS max to be a more reliable indicator of total SO 2 release.…”
Section: Caveats and Sources Of Error Of The Petrological Methodsmentioning
confidence: 99%
“…Actual volcanic volatile emissions may additionally involve input from magmatic S‐bearing volatile phases or external sources of volatiles (see Section 5.2). The petrological method also neglects post‐eruptive outgassing from cooling lava, which is an additional source of volcanic pollution (Donovan et al., 2023; Óskarsson et al., 1984; Pfeffer et al., 2018; Sigmarsson et al., 2020; Simmons et al., 2017; Thordarson et al., 1996). This process disproportionately affects F and Cl, which have initial concentrations far below their melt saturation values.…”
Section: Methods and Catalog Informationmentioning
confidence: 99%
See 1 more Smart Citation